BS IEC 61753-089-02. Fibre optic interconnecting devices and passive components. Performance standard. Part 089-02. Non-connectorized single-mode bidirectional OTDR monitoring WWDM devices for category C. Controlled environment (4th December 2020) - British Standards Institution,
No abstract available